Respons Pesindhen dan Qari’ Terhadap Lantunan Al-Qur’an Langgam Jawa - A’yun, Sevi Qurrotu; Maarif, Samsul; Suryati, Suryati; Jati, Galih Pangestu (Resital: Jurnal Seni Pertunjukan, 2024)
Javanese Qur'an chants performed by Yaser Arafat at the State Palace in 2015 during the commemoration of Isra' Mi'raj. The use of Javanese musicals influenced the formation of Javanese cloves in his singing. Javanese cloves as decorations for chanting the Qur'an should be able to make people who listen to it interested. However, in fact it caused controversy. This study aims to determine the Javanese clove formed and the response of a pesindhen and qari'-qari'ah to the chanting of the Javanese Qur'an. The research method used is a qualitative research method with a a musicological approach and case studies. This research has the object to be studied, namely the chanting of QS. Al-Isra' verse 1 and QS. An-Najm verses 1-15. Data collection was carried out by means of desk-based research, interviews, documentation and literature studies which were analyzed musicologically and using the Miles and Huberman model. The results showed that the chanting of the Javanese Qur'an by Yaser Arafat found Javanese cloves in the form of luk. Luk was formed accidentally by adjusting the law of tajweed. Pesindhen's response still appreciates his chants even though only luk was found. However, it does not agree with the use of macapat Pangkur. Similarly, reciters do not approve of using macapat Pangkur in their chants. Meanwhile, the reciter gave a response that did not approve of his chanting because he adhered to the hadith and maqamat of Al-Arabiyyah.